The Essence and Methods of Resolving Land Disputes - CHUDYK-BILOUSOVA , Nadiia; TARANENKO , Liudmyla (University Scientific Notes, 2020)
It is proposed to consider land disputes as a special type of legal relationship, which is based on differences of subjects manifested in the emergence, implementation, change or termination of land rights, their protection in connection with the violation of rights and legitimate interests (or their recognition) of owners or users of land plots, including tenants and other subjects of land legal relations. It is established that the process of improving the existing mechanisms for resolving land disputes is ongoing, so it should take place through a system of legal, organizational and economic measures. Such measures must be taken by authorized subjects of land relations in the application of procedures for the protection of land rights and ensuring the effective use of land under the conditions specified by the legislation of Ukraine. Land disputes are defined as a conflict between the subjects of land relations, which need to be resolved in the manner prescribed by law. Its participants are the subjects of land relations: the state and its authorized bodies, individuals and legal entities, whose legal status is determined by the rules of land and civil law. The classification of land disputes by nature, depending on the grounds (methods) of occurrence, change or termination of the right to use the land plot, depending on the settlement mechanism, according to the level of dispute resolution is proposed. The expediency of improving the procedure for consideration and resolution of land disputes by strengthening the administrative procedure for resolving them is substantiated. Due to the effect of quarantine and deterioration of financial situation, the possibility of a person to go to court to resolve a land dispute is significantly limited. The expediency of developing methodological recommendations for united territorial communities on the mechanisms and procedure for resolving land disputes and methodological recommendations for internally displaced persons on the procedure for protection of land rights is proposed.
Keywords: land dispute; conflict; out-of-court method; court method; land dispute resolution; land ownership